The WBC/HDL ratio outperforms other lipid profiles in predicting mortality among ischemic stroke patients: a retrospective cohort study using MIMIC-IV data - Li Zou; Dong Sun; Lei Zhang; Yu Xie; Renwei Zhang; Huagang Li; Bitang Dan; Yumin Liu; Bin Mei (Frontiers in Neurology)
ObjectiveTo assess the prognostic value of lipid profiles and their ratios, particularly the white blood cell to high-density lipoprotein (WBC/HDL) ratio, for predicting 28-day and 1-year all-cause mortality in ischemic stroke patients admitted to the ICU.MethodsA retrospective cohort study was conducted using the MIMIC-IV ICU database, including 2,894 ischemic stroke patients. Lipid profiles—including total cholesterol, triglycerides, low-density lipoprotein, and high-density lipoprotein—and derived ratios were analyzed. Associations with mortality were assessed using Cox proportional hazards models adjusted for demographic and clinical factors. Restricted cubic spline and Kaplan–Meier survival analyses were utilized to explore the relationship between the WBC/HDL ratio and mortality risk.ResultsTraditional lipid profiles and their ratios were not significantly associated with 28-day or 1-year mortality. Conversely, an elevated WBC/HDL ratio was independently associated with increased mortality risk at both 28 days (hazard ratio: 2.198; 95% confidence interval: 1.864–3.225) and 1 year (hazard ratio: 3.163; 95% confidence interval: 2.947–3.334). Restricted cubic spline analysis demonstrated a linear relationship between the WBC/HDL ratio and mortality risk, while Kaplan–Meier analyses indicated significantly poorer survival outcomes for patients with higher WBC/HDL ratios.InterpretationThe WBC/HDL ratio is a superior prognostic marker for mortality in ischemic stroke patients admitted to the ICU, outperforming traditional lipid profiles. Incorporating this measure into clinical practice may enhance early risk stratification and guide targeted interventions.